2023
DOI: 10.4103/ijpvm.ijpvm_236_21
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Mortality of Hospitalized COVID-19 Patients in Asian and Western Countries: a Systematic Review and Meta-Analysis

Abstract: Background: The authorities recently emphasized the importance of dietary control for COVID-19 patients in hospitals. However, there is limited detail about the obesity and death of COVID-19 patients who are hospitalized in the Asian and Western countries. The aim of this study was to find the role of obesity and mortality of the hospitalized COVID-19 patients. A systematic review of the studies on obesity and mortality of hospitalized COVID.19 patients in the Asian and western countries. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“… 7 , 8 A systematic review of the studies on obesity and mortality of COVID‐19 patients in the Asian and western countries reported that the mortality of COVID‐19‐hospitalized patients is related to obesity. 9 The exact mechanism of the effect of obesity on patients with COVID‐19 is not yet clear. Obesity‐induced inflammation may play a crucial role in the immune system dysfunction in patients with COVID‐19.…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 8 A systematic review of the studies on obesity and mortality of COVID‐19 patients in the Asian and western countries reported that the mortality of COVID‐19‐hospitalized patients is related to obesity. 9 The exact mechanism of the effect of obesity on patients with COVID‐19 is not yet clear. Obesity‐induced inflammation may play a crucial role in the immune system dysfunction in patients with COVID‐19.…”
Section: Introductionmentioning
confidence: 99%